ANALISIS MASALAH KESEHATAN MENTAL DAN PSIKOSOSIAL PETUGAS PENDAFTARAN PASIEN DI RSUD KOTA MALANG PADA ERA PANDEMI COVID-19 TAHUN 2020 - Annisa Ayu Maulidhika; Chyntia Vicky Alvionita (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2021)
Coronaviruses are group of viruses that can cause disease in animals/humans. The COVID-19 outbreak is contagious and spreads rapidly can have impact on psychological stress and symptoms of mental illness. So far, the handling of mental health and psychosocial disorders has been more focused on the community than health workers. The lack of focus on the mental health of health workers has the potential to disrupt and even turn off health services and will affect the handling of the COVID-19 pandemic. This study aims to determine (1) Mental and Psychosocial Health of Patient Registration Officers at Regional General Hospitals (RSUD) in the 2020 COVID-19 Pandemic Era; (2) Identify the characteristics of respondents including gender, marital status, age, education; (3) Identifying mental and psychosocial health at the Patient Registration Officer at RSUD Malang City. This research uses a qualitative descriptive research type. The characteristics of the disease from the COVID-19 pandemic, increasing the atmosphere of general vigilance and uncertainty, who communicate directly with patients every day, due to various causes such as the rapid spread and transmission of COVID-19, the severity of symptoms it causes in given situation. segments, infected people, lack of knowledge about disease, and mortality among health workers.